A new algorithm for automating power supply of an AC traction network with a sectioning points on switches - L. A. German; A. Yu. Popov; A. V. Samorukov; D. V. Ishkin; D. V. Yakunin; K. S. Subkhanverdiev (Вестник Научно-исследовательского института железнодорожного транспорта)
The article considers modern sectioning points on contact network and determining the location of the damage, imthe switches, which differs by the introduction of new functions for plemented in the IntTer smart terminal. These new functions are determining a stable (or passing) short circuit in the disconnected deciding whether to perform a quick automatic restart of the circuit breakers after an emergency shutdown or finding the fault zone without testing the insulation of the contact network. The principle of operation of the functions under consideration is analyzed in the article. The limits of the optimum time of the current-free pause of the circuit breaker for automatic re-activation (AR) for each inter-substation zone are established. The paper describes the existing algorithm for automating power supply of an AC traction network (the normal reclosing algorithm) and indicates the unfavorable consequences from its application, in particular, related to the long time of the absence of voltage in the contact network. It was noted that the decision to reduce the voltage recovery time performed by introducing the function of determining the passing (or stable) short-circuit in the switched-off contact network in traction substations is due to the cost of additional high-voltage equipment and requires a rethinking. Thus, a new algorithm for automating the power supply of the traction network (the BAR algorithm) is presented, which is quite easily implemented at the modern sectioning post, which has voltage transformers for each supply line of the contact network, in contrast to the supply lines of the substation contact network and is caused by the transfer of the function of determining the passing (or steady ) short circuit to the sectioning point. In the article, the issue of performing the automatic reclosure of the power line of the traction substation is considered dependent on the successful operation of the BAR algorithm of the sectioning point. It is established that the most rational option is the implementation of a dependent automatic reclosing of a traction substation using telemechanics. The authors analyze the possibility of manufacturing compact sections of the ac contact network on the basis of single-phase re-closers OR-27.5 kV. It is noted that it is advisable to use a new automation scheme in conjunction with the sectionalization points on reclosers.